약물성 치은비대로 인한 병적인 치아 이동이 있는 환자에서 치주치료 이후 자발적 치아 이동을 보인 증례 - 최윤경(Youn-Kyung Choi); 정경화(Kyoung-Hwa Jung); 김소연(So-Yeun Kim); 전혜미(Hye-Mi Jeon); 최점일(Jeomil Choi); 이주연(Ju-Youn Lee); 주지영(Ji-Young Joo); 권은영(Eun-Young Kwon) (Journal of dental rehabilitation and applied science, 2017)
Anticonvulsants, calcium channel blockers and immunosuppressants are representative drugs related with gingival enlargement. Clinical signs and symptoms caused by drug-induced gingival enlargment frequently appear within 1 to 3 months after medication. At initial stage, it is limited to attached gingiva but may extend coronally and interfere with esthetics, mastication and speech. Interproximal spaces are common beginning area and pathologic teeth migration could be occurred by the lesion. Withdrawal or substitution of medication would be the most effective treatment of drug-induced gingival enlargement. However, periodontal treatment and further supportive periodontal therapy should be provided where change in medication is impossible. The present study reports the cases which show the resolution of inflammation with spontaneous teeth migration without change in medication. In all cases discussed in this report could be efficiently managed with proper periodontal treatment and further supportive periodontal therapy. 치은비대와 연관된 대표적인 3가지 약물은 항경련제, 칼슘 길항제, 면역 억제재 등이다. 약물성 치은 비대를 위한 치료에서 근본적인 원인인 약물 대체가 선행되면 재발의 위험 등은 훨씬 낮아지는 이점이 있으나, 대체가 어려울 때는 치주치료와 철저한 유지관리가 병행되어야만 한다. 본 연구에서는 약물성 치은비대로 병적인 치아 이동이 일어난 경우, 약물 교체 없이 치주 치료로 염증이 해소 되면서 자발적으로 치아 이동이 함께 일어난 증례를 보고하고자 한다. 본 증례의 환자들도 치주치료 이후 적극적인 정기 점검을 통해 안정적으로 유지될 수 있었다.